Identification and characterization of persistent human erythrovirus infection in blood donor samples - Candotti, Daniel; Etiz, Nermin; Parsyan, Armen; Allain, Jean-Pierre (Journal of virology, 2004)
The presence of human erythrovirus DNA in 2,440 blood donations from the United Kingdom and sub-Saharan Africa (Ghana, Malawi, and South Africa) was screened. Sensitive qualitative and real-time quantitative PCR assays revealed a higher prevalence of persistent infection with the simultaneous presence of immunoglobulin G (IgG) and viral DNA (0.55 to 1.3%) than previously reported. This condition was characterized by a low viral load (median, 558 IU/ml; range, 42 to 135,000 IU/ml), antibody-complexed virus, free specific IgG, and potentially infectious free virus. Human erythrovirus genotype 1 (formerly parvovirus B19) was prevalent in the United Kingdom, Malawi, and South Africa. In contrast, only human erythrovirus genotype 3 (erythrovirus variant V9) was prevalent in Ghana. Genotype 3 had considerable genetic diversity, clustering in two probable subtypes. Genotype 1-based antibody assays failed to detect 38.5% of Ghanaian samples containing antibodies to genotype 3 virus but did not fail to detect cases of persistent infection. This study indicates a potential African origin of genotype 3 human erythrovirus and considerable shortcomings in the tools currently used to diagnose erythrovirus infection.